Feasibility of Using Oscillatory Catalytic Oxidation Phenomenon for Selective Carbon Monoxide Sensing - Heikki Torvela (Active and Passive Electronic Components)
Tin dioxide based sensors with different additives were constructed and tested in air environment containing carbon monoxide. Conductance oscillations were observed in samples containing palladium but not in those without. Oscillations occurred at temperatures ranging from 150℃ to 320℃. Within this temperature region the range of CO concentrations at which oscillations appeared became higher as the test temperature increased. The lowest CO concentration at which oscillations were observed was 200 ppm and the highest 10000 ppm.